INTERAKSI KOMUNITAS ONLINE DALAM MERESPONS AKUNTABILITAS DAN TRANSPARANSI DONASI ONLINE: (STUDI NETNOGRAFI) - Muhamad Satriawan Alfarizi; Ayudia Sokarina (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to understand the responses of the online community toward the accountability and transparency practices of online donations mediated by the streamer figure Windah Basudara through the YouTube and Instagram platforms. Methods: This study employs a qualitative approach using the netnography method, in which data were collected in a lurker (passive) manner. The data were analyzed through the stages of Coding, Noting, and abstracting to capture collective meaning patterns that developed within community interactions.Results: The findings reveal that community responses are not homogeneous, but rather encompass appreciation, emotional admiration, respect, critical attitudes, curiosity regarding the donation flow, social aspirations, and emotional attachment to the streamer figure. These findings indicate that accountability and transparency in online donation practices are not solely constructed through formal reporting but also through dialogic interaction, openness to questions, and the emotional relationships continuously established between the streamer and the community. This study contributes to broadening the understanding of social accountability in the context of online donation fundraising conducted by influencers, by positioning the online community as an active actor in shaping, testing, and negotiating the meanings of accountability and transparency. Keywords: Accountability; Donations; Influencers; Streamers; Transparency.